Production prospects for cassava in Tanzania: COSCA working paper, No. 16 - Nweke, F.; Kapinga, R.; Dixon, A.; Ugwu, B.; Ajobo, O.; Asadu, C. (1998)
Several cassava genotypes were observed although there were few bred varieties. The wide diversity in the cassava landraces was a consequence of the action of the farmers in continuously abandoning and introducing cultivars into their system as they tried to select those cultivars that met their needs. These included extended in ground storability in remote areas, high lOOt yield, and earliness in high demographic pressure areas, low cyanogen level in specific areas where the sweet cassava type was needed, as well as their needs for pests/disease tolerance, and good processing qualities. All the landraces were of a local type with low genetic yield potential and did not seem to resist major pests/diseases of the cassava plant. Declining fallow periods constituted a constraint to expansion in cassava production; because of cassava's long growth cycle farmers were not able to grow the crop under Continuous cultivation as frequently as they were able to grow some other crops as they got low cassava yields. Cassava was more frequently used to close a rotation cycle where the crop was stored in fallow fields in remote areas with low demographic or market pressures. The crop was, however, more frequently used to open a rotation cycle under severe pest/disease pressure conditions, under high market pressure conditions where the crop was harvested early. And under conditions of free grazing of cattle where farmers were not able to store the crop in fallow fields. Cassava was intercropped more frequently than the average for other crops; however, within the intercrop, cassava was the major crop more often than other crops. Maize and beans or peas were most frequently intercropped with cassava. Other management practices, especially plant density and age at harvest, were not adopted at optimal levels; in high market pressure areas where superior practices were adopted, lOOt yield improved significantly. Cassava was produced with relevant purchased inputs as frequently as, and in some cases more frequently than other staples. The frequencies of use of hired labor and mechanized transportation were positively correlated with proximity to market centers. Cassava production did not respond positively in terms of high root yield and especially in terms of land area expansion because of the low frequencies of the use of the various purchased inputs. In addition, the incidence of cassava green mite (COM), an arthropod pest of the cassava plant which was widespread, must have discouraged farmers from expanding cassava land area. It could have also resulted in low yields, even in fields in which the purchased inputs were used, while farmers ranked cassava in order of relative importance based on the food security value of the crop, they allocated land to it based on its market value. Cassava was allocated relatively more farmland in areas where farmers had access to market or to improved postharvest handling facilities than elsewhere. Famine was not reported where cassava was relatively important.The range of cassava food products was narrow. Cassava was transformed predominantly into a non-convenient food product which could not compete effectively with food grains in the market and therefore did not have as many market opportunities as cassava food products made in other countries, especially in West or Central Africa. Farmers in remote villages who had access to mechanized processing facilities planted relatively more cassava for sale than farmers who had easy access to market centers. Farmers in the areas surveyed depended more on nonfarm activities and, to some extent, on industrial crops than on food crops for cash income. Cassava production was, however, more important than any other food crop as a source of cash income for the producing households. Cash income from the cassava production benefitted more households than cash income from any other food crop. The cassava production cash income was highest among farmers who had access to mechanized processing technology, or easy access to market centers, or among those who used purchased inputs in production. In conclusion, cassava production was declining in a large proportion of the producing villages because production was not positively linked with market; market access infrastructure was inadequate, processing methods were rudimentary, and the range of cassava food products was narrow. Hence, there was no market incentive to motivate farmers to adopt known superior agronomic management practices, or to use purchased inputs to expand land area. Cassava varieties available to the farmers have low genetic potential in yield and poor resistance to major pests and diseases.